PENGARUH MODEL PEMBELAJARAN SAVI TERHADAP HASIL BELAJAR SISWA PADA KONSEP SISTEM EKSKRESI MANUSIA - RISKA RAMADHANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research ained to analyze empirically the effect of the Somatic Auditory Visualization Intellectually (SAVI) learning model on student learning outcomes on the concept of the excretory system. The method used is a quasi-experimental research design with a non-equivalent control group design. This research was conducted at SMP Negeri 2 Cileles in May 2019. The samples used were class VIII B as the experimental class and class VIII A as the control class. Data collection was carried out using tests and observations. The results showed that there was a significant effect of the application of the SAVI model on cognitive, affective and psychomotor learning outcomes (p < 0.05) with an average cognitive ability acquisition of 79.0 for the experimental class and 44.8 for the control class. The affective ability of the experimental class is 79.6 and the control class is 65.0. Psychomotor ability in experimental class is 82.6 and control class is 65.0. Based on the results of research, processing and análisis of data, it can be concluded that the Somatic Auditory Visualization Intellectually (SAVI) learning model has an effect on students' cognitive, affective and psychomotor learning outcomes on the concept of the human excretory system in class VIII of SMP Negeri 2 Cileles. ABSTRAKPenelitian ini bertujuan untuk menganalisis secara empiris pengaruh model pembelajaran Somatic Auditory Visualization Intellectually (SAVI) terhadap hasil belajar siswa pada konsep sistem ekskresi. Metode yang digunakan yaitu quasy eksperiment dengan desain penelitian non equivalent control group design. Penelitian ini dilakukan di SMP Negeri 2 Cileles pada bulan Mei tahun 2019. Sampel yang digunakan kelas VIII B sebagai kelas eksperimen dan kelas VIII A sebagai kelas kontrol. Pengumpulan data dilakukan menggunakan tes dan observasi. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan penerapan model SAVI terhadap hasil belajar kognitif, afektif dan psikomotorik (p < 0,05) dengan perolehan rata-rata kemampuan kognitif kelas eksperimen 79,0 dan kelas kontrol 44,8. Kemampuan afektif kelas eksperimen 79,6 dan kelas kontrol 65,0. Kemampuan Psikomotorik kelas eskperimen 82,6 dan kelas kontrol 65,0. Berdasarkan hasil penelitian, pengolahan dan analisis data dapat disimpulkan bahwa model pembelajaran Somatic Auditory Visualization Intellectually (SAVI) berpengaruh terhadap hasil belajar kognitif, afektif dan psikomotorik siswa pada konsep sistem ekskresi manusia di kelas VIII SMP Negeri 2 Cileles.